2000
DOI: 10.1093/ije/29.4.645
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence of adenocarcinoma of the oesophagus and gastric cardia in ten European countries

Abstract: This study, using Eurocim data, supports the findings from other time-trend studies of population-based cancer registries in western countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
306
2
9

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 482 publications
(333 citation statements)
references
References 27 publications
15
306
2
9
Order By: Relevance
“…20 In the Netherlands and some countries, however, previous studies showed no increase in the incidence of cardia cancer. 21,22 Our results confirm this, although in the most recent period a small proportional rise was seen in cardia carcinoma. Some suggest that misclassification of distal oesophageal cancer as gastric cardia cancer explains the non-increasing incidence of cardia carcinoma.…”
Section: Discussionsupporting
confidence: 84%
“…20 In the Netherlands and some countries, however, previous studies showed no increase in the incidence of cardia cancer. 21,22 Our results confirm this, although in the most recent period a small proportional rise was seen in cardia carcinoma. Some suggest that misclassification of distal oesophageal cancer as gastric cardia cancer explains the non-increasing incidence of cardia carcinoma.…”
Section: Discussionsupporting
confidence: 84%
“…The incidence of oesophageal adenocarcinoma has risen at a greater rate than any other malignancy in the USA and most European regions, currently varying from one in 146 to one in 285 cases/patient/year (Drewitz et al, 1997;O'Connor et al, 1999;Botterweck et al, 2000;Nilsson et al, 2000;Conio et al, 2001). Adenocarcinoma of the oesophagus almost always arises as a consequence of the neoplastic progression of Barrett's oesophagus and has a poor prognosis, with 5-year survival rates of only 10% (Farrow and Vaughan, 1996).…”
mentioning
confidence: 99%
“…4 The incidence of these 2 types of cancers has progressively risen in the Western world. 2,[5][6][7][8] However, at the present time, it is impossible to predict which patients are at risk of neoplastic progression and all patients are advised to undergo a regular endoscopic followup. 9,10 BE patients have a 30 -125-fold increased risk of developing esophageal AC compared to the general population.…”
mentioning
confidence: 99%